Governing the Countryside: Microsocial Analysis and Institutional Construction in Late Eighteenth-Century Río de la Plata - Barriera, Dario Gabriel (2021)
At the end of the eighteenth century, the Hispanic Monarchy imagined new solutions for governing its territories between the south of the Amazon, the Strait of Magellan, and the Andean cordillera. Populated by farmers and shepherds, these huge rural areas remained poorly known to the authorities. Yet among the reforms conducted in America by Charles III?including the adoption of the intendancy system?none tackled the administration of the countryside head-on. This problem is key for two reasons. First, most of the population of the Río de la Plata lived in rural areas. Second, the enormous distances that separated these areas from the urban centers where representatives of the Monarchy resided (Santa Fe, Buenos Aires, or Madrid) posed a challenge that the authorities had to face in order to govern these populations. Shifting from a ?top-down? perspective to a ground-level analysis attentive to local dynamics makes it possible to shed new light on how these spaces far removed from the centers of power functioned. Through the microhistorical analysis of a series of institutional transformations affecting the Río de la Plata, this article shows how subjects came to participate in the government of their region, mobilizing their networks to create a community and institutions on a local scale.